2009
DOI: 10.1097/gim.0b013e318197a49a
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and nonrandom distribution of exonic mutations in interferon regulatory factor 6 in 307 families with Van der Woude syndrome and 37 families with popliteal pterygium syndrome

Abstract: Purpose: Interferon regulatory factor 6 encodes a member of the IRF family of transcription factors. Mutations in interferon regulatory factor 6 cause Van der Woude and popliteal pterygium syndrome, two related orofacial clefting disorders. Here, we compared and contrasted the frequency and distribution of exonic mutations in interferon regulatory factor 6 between two large geographically distinct collections of families with Van der Woude and between one collection of families with popliteal pterygium syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
165
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 124 publications
(189 citation statements)
references
References 47 publications
19
165
1
4
Order By: Relevance
“…We also identified a c.1234C>t mutation leading to p.R412X, a nonsense mutation in exon 9 (VWS4; Fig. 3A) that has been previously described in Brazilian and Northern European populations (6). No unique exonic missense, nonsense or frameshift mutations were found in our fifth family (VWS5), although a c.921C>t mutation resulting in a conserved serine to serine mutation was found in exon 7 in the affected sibling pair (p.S307S).…”
Section: Irf6 Mutationssupporting
confidence: 63%
See 1 more Smart Citation
“…We also identified a c.1234C>t mutation leading to p.R412X, a nonsense mutation in exon 9 (VWS4; Fig. 3A) that has been previously described in Brazilian and Northern European populations (6). No unique exonic missense, nonsense or frameshift mutations were found in our fifth family (VWS5), although a c.921C>t mutation resulting in a conserved serine to serine mutation was found in exon 7 in the affected sibling pair (p.S307S).…”
Section: Irf6 Mutationssupporting
confidence: 63%
“…using a protein structure damage predictor (Polyphen), this p.N88I mutation is thought to be damaging to the IRF6 protein structure. Asparagine 88 to histidine, tyrosine and serine mutations were previously described in VWS patients (5,6), further suggesting that this is an important conserved residue. Mutations at this site may alter IRF6 gene function, likely through dna-binding ability.…”
Section: Discussionmentioning
confidence: 69%
“…Primer sequences that were used to amplify exons 1 to 9 of IRF6 (RefSeq NM_006147.3) and PAX7 (RefSeq NM_001135254.1) have been published elsewhere (Ferreira de Lima et al. 2009; Butali et al. 2014a,b).…”
Section: Methodsmentioning
confidence: 99%
“…These variants are usually concentrated in the highly conserved DNA‐binding domain (exons 3 and 4) and less conserved transactivation domain (exons 7 and 9) (Ferreira de Lima et al. 2009). Recent sequence analyses of these four exons in VWS and PPS patients from Africa confirmed that these four exons are mutational “hot‐spots” in IRF6 (Butali et al.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in interferon regulatory factor 6 (IRF6), located on 1q32.2, are responsible for the two autosomal dominant orofacial cleft syndromes, Van Der Woude and popliteal pterygium syndrome [1][2][3]. It was also the first identified nonsyndromic orofacial cleft (NSOFC) susceptibility locus [4] and has been the only candidate gene consistently found to have a significant association with NSOFC across multiple studies in many regions of the world, for example, China and Europe [5][6][7].…”
Section: Introductionmentioning
confidence: 99%